Factors affecting dental service utilisation among older Singaporeans eligible for subsidized dental care – a qualitative study - Rakhi Mittal; Mun Loke Wong; Gerald Choon-Huat Koh; Desmond Luan Seng Ong; Yun Hui Lee; Mei Na Tan; Patrick Finbarr Allen (BMC Public Health, 2019)
Abstract Background The World Health Organization has highlighted the paucity of research into the oral health needs of older adults. In Singapore, until recently, publically funded/subsidized oral health care for adults has been limited to basic primary care at government-funded polyclinics. Access to a more comprehensive range of subsidized care in the private sector was widened through the government-funded Community Health Assistance Scheme (CHAS) in 2012 and Pioneer Generation (PG) scheme in 2015. Little is known about the attitude to dental service utilization among older adults in Singapore since then. Methods We conducted semi-structured individual interviews with 25 participants above 65 years of age who were eligible for subsidized dental care plans. Participants were recruited from a public teaching hospital and a public primary care clinic in Singapore. The duration of each interview was 15–30 min. Interviews were transcribed verbatim and the transcripts were analyzed thematically using a phenomenological approach. Results Pertinent themes emerged related to four major areas: (a) general awareness towards oral health, (b) life course perspective of oral health, (c) barriers to visit the dentist, (d) shaping dental service utilisation behaviours through provision of financial subsidies for dental care. Most participants perceived a strong relationship between oral health and systemic health. However, there were erroneous traditional beliefs such as oral health is not part of physical health and edentulous participants did not need to visit a dentist. Fear, anxiety, previous negative experience and lack of knowledge were barriers to visiting the dentist. Trust and convenience were considerations for patients when deciding whether to switch from public to private dental services where CHAS/PG were only available. Conclusion Our study provided important insights regarding oral health perceptions and beliefs of older people residing in the community which may affect their dental service utilization. This further highlights the importance of understanding the concerns of this group when implementing healthcare policies for elderly in Singapore. The findings of our study will serve as a baseline for future studies in Singapore and inform studies in other countries that implement targeted schemes for older adults.